The true story of J. Edgar Hoover and the FBI - Denenberg, Barry (New York : Scholastic Inc., 1993)
A biography of the former chief of the Federal Bureau of Investigation, focusing on the FBI's impact on the major law enforcement issues of the 1920s through the early 1970s.
Includes bibliographical references (p. 187-188) and index.
Keywords: Hoover, J. Edgar (John Edgar), -- 1895-1972 -- Juvenile literature; Hoover, J. Edgar (John Edgar), -- 1895-1972.; United States. -- Federal Bureau of Investigation -- History -- Juvenile literature; United States. -- Federal Bureau of Investigation -- History; Police -- United States -- Biography -- Juvenile literature; Police